ORGANIZATIONAL CLIMATE AND JOB SATISFACTION IN MICROFINANCE BANKS IN RIVERS STATE - Maxwell Nwinye (Scholars Digest Publishing, 2025)
This study examined organizational climate and job satisfaction in microfinance banks in Rivers State. Two hypotheses were formulated for the study. Population of the study covered 303 selected employees from 10 reachable microfinance banks in Rivers State. The researcher used explanatory survey design and random sampling method was applied for the purpose of minimizing research errors. The primary data was collected from structured questionnaire while the secondary data was information received from human resource data of various selected microfinance banks and Rivers State ministry of finance report. Taro Yamane’s formula was applied to discover a sample size of 172 employees. Copies of questionnaire were distributed to the listed participants. Spearman correlation coefficient was used to test the hypotheses. The findings of the study itemized that there was a positive significant relationship between organizational climate and job satisfaction in microfinance banks in Rivers State. It was also found that admirable workplace environment contributed to employee job satisfaction and organizational performance. The researcher recommended that microfinance banks should ensure that the organizational climate is designed to accommodate customers satisfaction, zero tolerance to delay of service, profitability, and employee job satisfaction.
Keywords: Organizational climate, workplace environment, job satisfaction.